A new species of the alpheid shrimp genus Thuylamea Nguyên, 2001 (Crustacea: Decapoda: Caridea) from Yatsushiro Sea, Kyushu, Japan - Komai, Tomoyuki (Zootaxa, 2018)
A new species of alpheid shrimp, Thuylamea shiranui, is described and illustrated on the basis of five specimens from Yatsushiro Sea, western Kyushu, Japan. It is closely related to T. camelus Nguyên, 2001, the type species of the heretofore monotypic genus Thuylamea Nguyên, 2001, known from South China, Vietnam and Singapore. The complete lack of submedian posterodorsal crests on the carapace and the relatively long antennular peduncle distinguish the new species from T. camelus. The generic diagnosis of Thuylamea is emended to accommodate the new species.